Investigation of the Effects of Life Skills Development Program in Children’s Libraries on Children’s Life Skills - Temiz, Nihan; Yılmaz, Bülent (Information World, 2024)
Children’s libraries are one of the most important out-of-school education and life centers. While providing services and applications to children, who are a special user group, there is a need for educational programs that are handled with interdisciplinary perspectives and developed in accordance with the children’s developmental levels, generation characteristics, special needs and the structure of the process they live in. This study was carried out to measure the effect of the “Library Life Skills Program”, which was created by including the development of life skills in children’s libraries, on children’s life skill levels. In the study conducted at Ankara Sincan Törekent Public Library Children’s Department with 57 children aged 5-6 (Experimental group: 30 children, Control group: 27 children), one of the quasi-experimental designs, “pretest-posttest design with balanced control group”, was used. In the study, the Library Life Skills Program, which was prepared by the researcher and consists of activities related to life skills, was applied to the experimental group in the library environment over a five-week period. The data of the research were obtained with the Checklist and Early Childhood Life Skills Scale, which consists of life skills defined by the World Health Organization. The findings showed that the Library Life Skills Program applied to the children in the experimental group created a significant statistical difference on the children’s life skills levels.
Keywords: Early childhood period; children’s libraries; life skills; library program; library services